(untitled) (Indian Journal of Arid Horticulture, 2025)
An experiment was conducted at JGKV, Raipur to assess the suitability of aonla cullivar viz. Banarsi, Chakaiya, Francis. Kanchan, Krislma, NA-10, NA-6 and NA-7 for preparation of squash and their shelflife. A recipe of 40 per cempulp, 60 per cent total soluble solids and 0.75 per cent acidity was found most ideal to prepare squash from Aon la. Among all the eight cultivars of aonla "Chakaiya" was found most suitable cullivar for preparation of squash. This squa h remained acceptable up to period of six months during storage al room temperature. The total soluble solid, acidity, reducing sugar and total sugar of lhe squash increased continuously duri.ng storage while the ascorbic acid in contrast decreased.